Assessing Mediating Effect of National Culture on the Relationship of Leadership Style with UAE Smart Government Organizational Performance - Almansoori, Khalid Abdulla Ibrahim; Ahmad, Ahmad Nur Aizat (International Journal of Sustainable Construction Engineering and Technology, 2023)
This study presents persuasive evidence that national culture acts as a mediator in the relationship between leadership style and organisational performance in the context of UAE Smart Government. By investigating these links, the study emphasises the importance of taking cultural aspects into account when evaluating the impact of leadership on organisational outcomes in the context of smart governance. Data collected through questionnaire survey was used to develop a PLS-SEM mediation model in SmartPLS software. The modelling analysis found that national culture partially mediates the leadership styles with the organisational performance. It further found that Abu Dhabi's smart government had low worker productivity requirements and lacked a strong national culture. Leadership has a major and positive impact on the organization's national culture. As a result, it is acceptable to claim that leadership style has a substantial impact on organisational procedures. According to studies, there is a link between national culture and organisational performance. The findings indicate a connection between leadership styles and the nation's commitment, cohesion, and mission. This implies that an organisational culture in which employees participate in important organisational decisions, that is consistent in its workplace practises, and that is motivated by a clear mission, ultimately affects the organisational performances of employees in such organisations.